2022
DOI: 10.1371/journal.pone.0268762
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput image-based plant stand count estimation using convolutional neural networks

Abstract: The landscape of farming and plant breeding is rapidly transforming due to the complex requirements of our world. The explosion of collectible data has started a revolution in agriculture to the point where innovation must occur. To a commercial organization, the accurate and efficient collection of information is necessary to ensure that optimal decisions are made at key points of the breeding cycle. In particular, recent technology has enabled organizations to capture in-field images of crops to record color… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…If the images are acquired too early, the seedlings are too small to be detected and counted, e.g., seedling detection and counting at T1 in this study. If the images are acquired too late, the cotton seedlings reach the four-leaf stage, and the leaves have spread out, with crossing and overlap occurring between leaves, resulting in underestimation of the cotton population, e.g., seedling detection and counting at T6 in this study, which are also the two significant challenges encountered so far [51]. Due to the short window of cotton seedlings, if the best time to replenish them is missed, it will affect the cotton yield at the later harvest.…”
Section: Discussionmentioning
confidence: 98%
“…If the images are acquired too early, the seedlings are too small to be detected and counted, e.g., seedling detection and counting at T1 in this study. If the images are acquired too late, the cotton seedlings reach the four-leaf stage, and the leaves have spread out, with crossing and overlap occurring between leaves, resulting in underestimation of the cotton population, e.g., seedling detection and counting at T6 in this study, which are also the two significant challenges encountered so far [51]. Due to the short window of cotton seedlings, if the best time to replenish them is missed, it will affect the cotton yield at the later harvest.…”
Section: Discussionmentioning
confidence: 98%
“…From the literature, it was found that there are many ML studies [10][11][12][13][14] and DL studies [39-43] have been proposed for finding and counting oil palm trees, to estimate yields, monitor crops, and identify nutritional deficiencies etc. However, comprehensive (monitoring growth and counting the healthy and unhealthy plantlings of palm tree with high accuracy) study on palm tree plantlings is yet to be researched.…”
Section: Plos Onementioning
confidence: 99%
“…Numerous research on useful resources and ML methods for the palm oil sector was undertaken. Research has investigated the use of remote sensing, breeding, and technology to keep tabs on palm oil farms [11]. Bioenergy manufacturing technologies for dealing with fruits and palm oil waste have been evaluated in another research [12].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this cross-over are presented in Table 2 , where despite semantic differences, the research fundamentals between plant science and weed recognition are common. Khaki et al (2022a) recognise this opportunity for the generalizability of a stand count approach in maize to contribute to weed detection, which could be combined with works such as Picon et al (2022) for maize extraction within weedy environments. Recognising the potential for research overlap, Weyler et al (2021) present a crop-weed detection system, which incorporates leaf counting for growth stage estimation and in-field phenotyping.…”
Section: Similarities Between Phenotyping and Weed Recognitionmentioning
confidence: 99%